Long Non-Coding RNAs H19 and HOTAIR Implicated in Intervertebral Disc Degeneration - Wang, Zhun; Zhang, Jingwei; Zheng, Wei; He, Yongjin (Frontiers in Genetics, 2022)
Objective: Intervertebral disc degeneration (IDD) is the major cause of low back pain. We aimed to identify the key genes for IDD pathogenesis. Methods: An integrated analysis of microarray datasets of IDD archived in public Gene Expression Omnibus was performed. Bioinformatics analyses including identification of differentially expressed mRNAs/microRNAs/long non-coding RNAs (DEMs/DEMis/DELs), pathway enrichment, and competitive endogenous RNA (ceRNA) network construction were performed to give insights into the potential functions of differentially expressed genes (DEGs, including DEMs, DEMis, and DELs). The diagnostic value of DEMis in distinguishing IDD from normal controls was evaluated through receiver operating characteristic (ROC) analysis. Results: DEGs were identified in IDD, including H19 and HOTAIR. In the DEMis–DEMs network of IDD, miR-1291, miR-4270, and miR-320b had high connectivity with targeted DEMs. Cell death biological processes and the JAK–STAT pathway were significantly enriched from targeted DEMs. The area under the curve (AUC) of 10 DEMs including miR-1273e, miR-623, miR-518b, and miR-1291 in ROC analysis was more than 0.8, which indicated that those 10 DEMs had diagnostic value in distinguishing IDD from normal individuals. Conclusions: DELs H19 and HOTAIR were related to IDD pathogenesis. Cell death biological processes and the JAK–STAT pathway might play key roles in IDD development.